Perlindungan Hukum Bagi Anak Dalam Tindak Pidana Pencurian Dengan Kekerasan Yang Mengakibatkan Matinya Korban (Studi Putusan No. 37/Pid.Sus-Anak/2017/PN. Mdn) - Tengku Fachreza Akhbar A; Maswandi Maswandi; Arie Kartika (JUNCTO: Jurnal Ilmiah Hukum, 2019)
Protection of children as perpetrators of crime will never stop throughout the history of life, because children are the next generation of the nation and the next generation of development, that is, the generation prepared as subjects for implementing sustainable development and controlling the future of a country. This type of research is normative juridical and descriptive analyst. The legal arrangements for the theft of violence with the result that the death of a victim is regulated in Article 365 of the Criminal Law Act, linked to Law 35 of 2014 Amendment to Law No.23 of 2002 concerning Child Protection, and Law No. 11 of 2012 Amendment to Law No. 3 of 1997 concerning Juvenile Courts. Legal protection that children get protection, accompanied by a Legal Counsel, Psychologist, the existence of peace efforts between the parties concerned. Sanctions and sentences in Decision No. 37 / Pid.Sus-Anak / 2017 / PN. Mdn because the perpetrators violated Article 365 paragraph (4) of the Criminal Code, considering Law Number 11 of 2012 concerning the Criminal Justice System for Children, the offender was sentenced to a prison sentence of six years.